Land Reform in Sub-Saharan Africa: Exploring Interested Parties Perspectives on Cameroon's Land Tenure and Land Law Reform. - Kenfack Kenjio, Jacques Wilfried (Antioch University, 2023)
This research study seeks to understand interested parties’ perspectives on Cameroon's existing land tenure systems, the 1974 land law, and ongoing efforts to reform this land law. It identifies both concerns and specific recommendations from these parties on the formulation and implementation of future reforms. In the decades following the achievement of independence from European colonizers, most governments in sub-Saharan Africa (SSA) have adopted new national land tenure policies to meet their countries’ needs and aspirations. In some parts of SSA, however, this process of land tenure formalization has negatively impacted the land rights of people observing customary land tenure. This has been a result of government interventions such as compulsory land acquisitions, which while technically legal, are ethically questionable. In the face of this challenge, efforts to reform post-colonial land laws have become a matter of urgency. A national land reform process for Cameroon, announced in 2011 has adopted a multistakeholder approach. My study seeks to understand interested parties’ perspectives on Cameroon’s existing land tenure systems, the 1974 land law, and ongoing efforts to reform the land law. This study applied a case study methodological approach and a convergent mixed-method design. Evidence from this study shows that interested parties in Cameroon are in agreement on 1) the reform of the 1974 land law, 2) the recognition of customary land tenure, 3) the continued use of multistakeholder participation in land law reform, and 4) the promulgation of the new land law through mass sensitization and information dissemination.
URI: http://rave.ohiolink.edu/etdc/view?acc_num=antioch1684431556060359
Keywords: Government-Driven Land Dispossessions; Land Expropriations; Land Law; Land Reform; Land Tenure; Mixed Methods; Multistakeholder Participation; Sub-Saharan Africa

Water as public property : a parallel evaluation of South African and German law - Viljoen, Germarié (North-West University, 2016)
With the introduction of the National Water Act 36 of 1998 (NWA) in South Africa’s water regulatory regime, the foundations of the country’s existing water law system changed fundamentally. The NWA was promulgated with the primary aim to reform the law relating to water resources. The preamble to the NWA states that water is “a scarce natural resource that belongs to all people.” Section 3 of the NWA continues along similar lines and stipulates that all water use rights fall under the centralised control of the state or public trustee to inter alia improve the distribution, management, use, conservation and equality of access to this scarce resource. Statutory transformation of this nature has inevitable and important legal implications. It has for example been argued that the changed system has brought about a reallocation and redefinition of property rights to natural resources; a transformation which will inevitably impact the nature, form, extent, limits and protection of access and use rights that can be acquired in water as a natural resource. In an effort to understand the extent of the legal transformation brought about by the concept of public trusteeship, this thesis considers the impact of the concept in the broader South African water law context. The concept of public trusteeship is a novel concept in South African jurisprudence, without established links to existing principles of law. This thesis subsequently focuses on how and to what extent the German property law concept of őffentliche Sache may inform the development and interpretation of the South African concept of public trusteeship as entrenched in the NWA. Consequently, this thesis commences with an exposition of information on the idea of property and the relevance and importance of the different property rights regimes against which both the South African and German property regimes can be evaluated. This is followed by a description of the South African property rights paradigm and its different property concepts. The research introduces a novel take on the discussion of the regulation of rights in natural resources in South Africa, namely a “stewardship ethic of public trusteeship”. As a stewardship ethic could potentially influence the regulation of property in natural resources and even perhaps the property regime within which water as natural resource is regulated in South Africa, the next section of the research proceeds with a historical account of the South African water law dispensation. Although the historical review indicates that the concept of public trusteeship is not part of South Africa’s common law heritage, some of its principles find application in the common law concept of res publicae. The conclusion is that the concept of public trusteeship does not merely (re-) introduce the res publicae concept into the South African water realm. The concept of public trusteeship is a novel concept that was statutorily introduced into the South African water regulatory framework in terms whereof “ownership” of water resources vests in the national government, and are consequently administered on behalf of the nation and generations yet to come. A separate section of the research analyses and contextualises the concept of őffentliche Sache as it functions in German law to offer new insight into the implications that the statutorily introduced concept of public trusteeship might have on water as property and the property regime within which water is regulated in South Africa. This guides the study to the next section of the research, which illustrates that the concept of őffentliche Sache is at the basis of the German water regulatory framework. The conclusion of the study proposes an understanding of the concept of public trusteeship in South Africa based on lessons learned from the German concept of őffentliche Sache.
Keywords: Constitutional property; German water regulatory framework; National Water Act; Property; Property rights regime; Public property; Public trusteeship; Res publicae; Water rights; Öffentliche Sache